My seditious heart : collected non-fiction - Arundhati Roy (Penguin Books, 2019)
"In constant conversation with the themes and settings of her novels, the essays form a near-unbroken memoir of Arundhati Roy's journey as both a writer and a citizen, of both India and the world, from "The End of Imagination", which begins this book, to 'Azadi', with which it ends. Bookended by her two award-winning novels, The God of Small Things (1997) and The Ministry of Utmost Happiness (2017), My Seditious Heart collects the work of a two-decade period when Arundhati Roy devoted herself to the political essay as a way of opening up space for justice, rights, and freedoms in an increasingly hostile world. Taken together, the essays speak in a voice of unique spirit, marked by compassion, clarity, and courage. Radical and superbly readable, they speak always in defense of the collective, of the individual and of the land, in the face of the destructive logic of financial, social, religious, military, and governmental elites"--